The gruffalo's child - Donaldson, Julia; Scheffler, Axel (Macmillan Children's London, 2005)
This story, told in rhyme, describes how the Gruffalo's Child ignores her father's warning and tiptoes out into the snowy wood. After all, the Big Bad Mouse doesn't really exist ... does he?